Comprehensive survey on support policies and optimal market participation of renewable energy - Cicek, Alper; Guzel, Semih; Erdinc, Ozan; Catalao, Joao P. S. (ELSEVIER SCIENCE SA, 2021)
Energy demand in the world is mostly met by conventional sources that cause carbon emissions. Considering environmental problems and the depletion of these sources in the near future, there is a trend towards renewable energy sources (RESs). Also, countries are implementing policies such as investment support, production support, quantity target, and limiting carbon emissions to increase the number of RESs. When these policies are compared, one of them can be superior to another in different countries. Also, superficial supports can cause an excessive financial burden on the governments. RESs have inherently intermittent power generation and in this respect, it is important to correctly estimate the RESs whose production changes with environmental conditions and to offer to the electricity markets optimally. For this reason, it is also important to know the structures of the electricity markets in bidding. Besides, RESs can come together to take an effective position in the market in terms of price and manage their imbalances. These structures can take names such as aggregator, virtual power plant (VPP), and portfolio. Considering the above-mentioned issues, this study aims to investigate in detail the methods applied to increase the number of RESs and the ways these resources participate in the electricity markets. In this context, subjects of policies promoting RESs, electricity market structures, development of the electricity market, optimum bidding strategy and ways of collective participation of RESs in the electricity markets are comprehensively examined under different sections.
Keywords: Electricity market; Optimal bidding; Renewable energy policies; OPTIMAL BIDDING STRATEGY; FEED-IN-TARIFF; VIRTUAL POWER-PLANTS; ENVIRONMENTAL/TECHNO-ECONOMIC APPROACH; ELECTRIC VEHICLE AGGREGATOR; TRADABLE GREEN CERTIFICATES; SUPPLY FUNCTION EQUILIBRIUM; GAP DECISION-THEORY; WIND POWER; ROBUST OPTIMIZATION; Engineering